Architectural Design is the Governing Law of Architecture Between Futurism and Adaptation (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Architecture is one of the subjects given to human knowledge. Architecture is situated in the field of attraction between subject and object, where it is within the framework of the perceived subject and at other times within the framework of the perceiving subject, the creator or reader of it. This dialogue attempts to find a law that "guarantees architecture's future adaptability." This is achieved by shedding light on the approaches through which conflicting architectural ideas can be understood, leading to an understanding of the truth of architecture, such as (the rational approach, the experimental approach, the deductive approach, the abstract approach). This dialogue relies on studying the interconnected relationship between terms that express the rational approach (instinct, universals, prediction) and other terms that represent the material approach (experience, particulars, certainty). Then, the reciprocal relationship between them is studied to arrive at an adaptable architecture. Sources of Perception: ((The sources of human knowledge are divided into two basic types: (sources of perception and sources of belief((.